Tropical rain forests around the world - Landau, Elaine (New York : F. Watts, 1990)
Discusses the environmental conditions of rain forests, the plants and animals that live in these forests, and the dangers of deforestation.
Includes bibliographical references.
Booklist.
School Library Journal.
4.5
4-6.
5-8
Keywords: Rain forest ecology -- Juvenile literature; Rain forests -- Juvenile literature; Ecology; Forest ecology; Rain forest ecology; Rain forests; Forest ecology; Rain forest ecology; Rain forests